Associations Between Government Ownership, Leverage, Media Exposure, Environmental Performance, and Carbon Emission - Pistrikayani, Ni Komang; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p10, 2024)
This study seeks to provide empirical evidence on the impact of government ownership, leverage, media exposure, and environmental performance on carbon emission disclosure. The research focuses on energy sector companies listed on the IDX from 2018 to 2022. The sample was selected using purposive sampling, resulting in eight companies and 40 observations. Multiple linear regression analysis reveals that media exposure positively influences carbon emission disclosure, while government ownership, leverage, and environmental performance show no significant effects. These findings support legitimacy theory, indicating that companies with greater media exposure are more transparent in their carbon emission reporting. Keywords: Carbon emission disclosure; government ownership; leverage; media exposure; environmental performance.